A new species of Diacheopsis from Russia - Vlasenko, Anastasia V.; Vlasenko, Vyacheslav A.; Kabilov, Marsel R. (Phytotaxa, 2022)
Diacheopsis is a small genus of myxomycetes with about 18 species reported around the world. Diacheopsis species are recorded in Eurasia, North and South America, Australia and New Zealand. A new species of Diacheopsis from coniferous forest of Asian part of Russia is described and illustrated. The new species occurred on a dead tree of Pinus sylvestris. It differs from all known species of the genus Diacheopsis in the sporocarps being drab grey, beige colours and the spores have warts up to 0.4 µm in total height. By SEM observations the warts are dense, abundant and regularly distributed, well-developed, with coralloid projections on the apex of each wart. Sequences for SSU rDNA of the new Diacheopsis species were generated. Preliminary phylogenetic analyses based on partial 18S rDNA sequences support the establishment of the new species.